Fasting enhances pyroglutamyl peptidase II activity in tanycytes of the mediobasal hypothalamus of male adult rats - Lazcano, I. (2015)
Fasting down-regulates the hypothalamus-pituitary-thyroid (HPT) axis activity through a reduction of TRH synthesis in neurons of the parvocellular paraventricular nucleus of the hypothalamus (PVN). These TRH neurons project to the median eminence (ME), where TRH terminals are close to the cytoplasmic extensions of β2 tanycytes. Tanycytes express pyroglutamyl peptidase II (PPII), the TRH-degrading ectoenzyme that controls the amount of TRH that reaches the anterior pituitary. We tested the hypothesis that regulation of ME PPII activity is another mechanism by which fasting affects the activity of the HPT axis. Semiquantitative in situ hybridization histochemistry data indicated that PPII and deiodinase 2 mRNA levels increased in tanycytes after 48 hours of fasting. This increase was transitory, followed by an increase of PPII activity in the ME, and a partial reversion of the reduction in PVN pro-TRH mRNA levels and the number of TRH neurons detected by immunohistochemistry. In fed animals, adrenalectomy and corticosterone treatment did not change ME PPII activity 72 hours later. Methimazole-induced hypothyroidism produced a profound drop in tanycytes PPII mRNA levels, which was reverted by 3 days of treatment with T4. The activity of thyroliberinase, the serum isoform of PPII, was increased at most fasting time points studied. We conclude that delayed increases in both the ME PPII as well as the thyroliberinase activities in fasted male rats may facilitate the maintenance of the deep down-regulation of the HPT axis function, despite a partial reactivation of TRH expression in the PVN.